Pensamento ecosófico: receitas site specific para uma cura da terra - Briotto, Luciane (2019)
This work is the written material of the performance and political experience carried out during five years at the Producer's Fair at the Água Branca Park, São Paulo. The research is condensed in the form of texts marked by the concept of Ecosophy. It focuses on food as a process and content of the chain of affective forces as well as its role in the creation of relational policies. The research explores food as a device in the process of reflection and provides knowledge about the functioning modus of individual bodies, including the psychological and physiological aspects in resonance. In the social fabric, food, as a dynamo, creates and recreates policies for the maintenance of lives, cultures and/or tanatopolitics for the extermination of certain minority populations chosen by the criterion of market interests. The reinvention of a new way of life is urgent. Climate change and the increasing rise in global temperatures may soon put the process of large-scale food production into jeopardy. Food is power and a part of the reflective chain of human creation, adding body - culture - thought. The research raises the possibility of approaching - as a strategy of resistance - an animist thought that places human matter on a horizontal plane alongside other manifestations of non-human lives. This exercise is an attempt to articulate a less violent way of thinking and its potential to change the way we relate to the planet, to launch ourselves into the proposition of affirmative powers, to make the transition from the status of consumers to that of co-creators of planetary life